Survey of adherence to sepsis care bundles in six European countries shows low adherence and possible patient risk - Ron Daniels; Mark Miller; Ellie Foot; Sophie Pittaway; Serena Urzi; Arnaud Favry (BMJ Open Quality)
Sepsis is a life-threatening condition which globally claims more lives than cancer. A set of evidence-based clinical practices (sepsis bundles) have been developed to guide early diagnosis and rapid intervention, which are vital to patient survival; however, their use is not widely adopted. A cross-sectional survey was administered in June–July 2022 to understand healthcare practitioner (HCP) knowledge of and adherence to sepsis bundles and identify key barriers to adherence in the UK, France, Spain, Sweden, Denmark and Norway; a total of n=368 HCPs ultimately participated. The results showed that among HCPs, overall awareness of sepsis and the importance of early diagnosis and treatment is high. However, there are indications that adherence to sepsis bundles is well below the standard of care: when asked which steps providers carry out to treat sepsis, only 44% report carrying out all steps in the bundle; and 66% of providers agreed that delays in sepsis diagnosis occur sometimes where they work. This survey also highlighted the possible barriers which are impeding the implementation of optimal sepsis care: particularly high patient caseload and staff shortages. This research highlights important gaps and obstacles in reaching optimal care of sepsis in the surveyed countries. There is a need for healthcare leaders and policy-makers alike to advocate for increased funding for more staff and training to address existing knowledge gaps and improve patient outcomes.